2011
DOI: 10.7589/0090-3558-47.4.821
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coxiella Burnetii in Western Grey Kangaroos (Macropus Fuliginosus) in Western Australia

Abstract: We investigated the role of the western grey kangaroo (Macropus fuliginosus) in the maintenance and transmission of Coxiella burnetii in Western Australia. Sera from 1,017 kangaroos were tested using an indirect enzyme-linked immunosorbent assay (ELISA) for the presence of C. burnetii antibodies. The overall antibody prevalence across 12 locations throughout mid- to southwestern Western Australia was 24.1% (95% CI: 21.6-26.8). Feces from 990 of the same animals were tested using PCR to identify active shedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Infected ruminant females shed large burdens of C. burnetii upon delivery and/or in the remains of miscarriages and in faeces, vaginal mucus, urine and milk . General shedding by any of those routes can last several months (Berri, Rousset, Champion, Russo, & Rodolakis, 2007) and occurs even in asymptomatic animals (Rousset et al, 2009) , 2017;Potter et al, 2011;Stein & Raoult, 1999;To et al, 1998). These findings show that shedding routes in wildlife resemble those reported in domestic ruminants (see Maurin & Raoult, 1999), which may guide future studies.…”
Section: And Transmission In Wildlifesupporting
confidence: 56%
See 2 more Smart Citations
“…Infected ruminant females shed large burdens of C. burnetii upon delivery and/or in the remains of miscarriages and in faeces, vaginal mucus, urine and milk . General shedding by any of those routes can last several months (Berri, Rousset, Champion, Russo, & Rodolakis, 2007) and occurs even in asymptomatic animals (Rousset et al, 2009) , 2017;Potter et al, 2011;Stein & Raoult, 1999;To et al, 1998). These findings show that shedding routes in wildlife resemble those reported in domestic ruminants (see Maurin & Raoult, 1999), which may guide future studies.…”
Section: And Transmission In Wildlifesupporting
confidence: 56%
“…General shedding by any of those routes can last several months (Berri, Rousset, Champion, Russo, & Rodolakis, ) and occurs even in asymptomatic animals (Rousset et al., ). Shedding routes in wildlife include: (a) genital secretions as proven in red deer, European wild rabbit, Eurasian wild boar and small mammals ( Napaeozapus insignis , Peromyscus maniculatus , Microtus arvalis , Myodes gapperi , Tamiasciurus hudsonicus , Glaucomys sabrinus and Glaucomys volans ) (González‐Barrio, Martín‐Hernando, & Ruiz‐Fons, ; González‐Barrio, Almería, et al., ; González‐Barrio, Maio et al., ; González‐Barrio, García et al., ; Thompson, Mykytczuk, Gooderham, & Schulte‐Hostedde, ); (b) milk and/or mammary gland as shown for the red deer (González‐Barrio, Ortiz, & Ruiz‐Fons, ); (c) semen of dorcas gazelle ( Gazella dorcas ) (García‐Seco et al., ); and (d) faeces as demonstrated for the Australian western grey kangaroo ( Macropus fuliginosus ), the three‐toed sloth ( Bradypus trydactilus ), the red deer and the Eurasian wild boar (Banazis, Bestall, Reida, & Fenwick, ; Davoust et al., ; González‐Barrio, Martín‐Hernando et al., ; González‐Barrio, Ortiz et al., ; Potter et al., ; Stein & Raoult, ; To et al., ). These findings show that shedding routes in wildlife resemble those reported in domestic ruminants (see Maurin & Raoult, ), which may guide future studies.…”
Section: Coxiella Burnetii Pathogenicity and Transmission In Wildlifementioning
confidence: 99%
See 1 more Smart Citation
“…Infection of stock in Gippsland may be occurring through direct contact with infected stock, importation of infected stock from interstate and elsewhere in Victoria, transmission on fomites or via environmental contamination. Local native wildlife may also be providing a reservoir for infection, which spills over into ruminants, thereby exposing people. Serological surveys of livestock and wildlife in Victoria would clarify the public health and production risks.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because a recent survey regarding zoonoses indicated that 64.5% of respondents did not consider themselves at risk of being infected from pet animals showing a lower level of awareness of the possibility of infection from these animals (Steele & Mor 2015). In addition, there is evidence of infection in other animal species such as horses, dogs (Tozer, S. J. et al 2014), wild animals and their ticks, and (Cooper et al 2013) marsupials (Potter et al 2011).…”
Section: Reservoirsmentioning
confidence: 99%